Lignocellulosic Materials and Their Use in Bio-based Packaging - Ballesteros, Lina Fernanda; Michelin, Michele; Vicente, António Augusto; Teixeira, José António; Cerqueira, Miguel Ângelo (Biobased Polymers, 2018)
This brief provides a comprehensive review of lignocellulosic materials and their primary role in the future development of bio-based packaging. Topics such as: sources and extraction methods of lignocellulosic materials; main constituents of lignocellulosic materials; functionality of lignocellulosic materials; the development of bio-based and biodegradable packaging; incorporation of lignocellulosic materials in bio-based packaging materials; properties and functionality of bio-based packaging, are discussed by authors who are experts in the field. .